A Multimessenger View of Galaxies and Quasars From Now to Mid-century - D'Onofrio, Mauro; Marziani, Paola (Frontiers in Astronomy and Space Sciences, 2018)
In the next 30 years, a new generation of space and ground-based telescopes will permit to obtain multi-frequency observations of faint sources and, for the first time in human history, to achieve a deep, almost synoptical monitoring of the whole sky. Gravitational wave observatories will detect a Universe of unseen black holes in the merging process over a broad spectrum of mass. Computing facilities will permit new high-resolution simulations with a deeper physical analysis of the main phenomena occurring at different scales. Given these development lines, we first sketch a panorama of the main instrumental developments expected in the next thirty years, dealing not only with electromagnetic radiation, but also from a multi-messenger perspective that includes gravitational waves, neutrinos, and cosmic rays. We then present how the new instrumentation will make it possible to foster advances in our present understanding of galaxies and quasars. We focus on selected scientific themes that are hotly debated today, in some cases advancing conjectures on the solution of major problems that may become solved in the next 30 years.